The Friction between Faculty Evaluations and Rewards: Reconsidering Teaching's Rhetoric and Recognition - Nicole Womack (Park University, 2013)
Educators know the reality and the inadequacies of current evaluation systems - there are gaps between what is defined as good teaching, how faculty members are assessed, and how they are rewarded (or not) for their work in the scholarship of teaching and learning. Student evaluations are ineffective tools to assess teachers. Educators must be given the opportunity to show their work and achievements and to develop a rich community of support, but they also must be evaluated in various formats to provide the best learning opportunities for students.